PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI ANDROID BERBASIS PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI BANGUN RUANG BAGI SISWA KELAS VI - Mokhamad Taufik; Ida Dwijayanti; Rasiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This research is motivated by the low learning outcomes of formative tests in Mathematics learning materials for class VI SDN Keteleng 01 based on observations and interviews with class teachers. This study aims to produce Problem Posing-Based Android Application media to improve learning outcomes in geometric material. The type of research used is Thiagarajan Semmel and Semmel's 4-D (Four-D) development research. The data collection method used is the method of observation, questionnaires and tests. Data were analyzed by descriptive quantitative. The results of the research at the defining and design stages produce an Android application design which in its presentation uses the Problem Posing syntax. Then the development stages were carried out, namely by expert validation, practicality tests and effectiveness tests on digital book media, picture series based on examples non examples. The results of the media expert validity test got an average score of 90% with very good criteria and 90.5% according to material experts with very good criteria. The results of the practicality test based on student responses got an average score of 92.00% and 90% based on the teacher's response with very good criteria. The effectiveness of Problem Posing Based Android Application media was tested valid based on the t test to get a sig (2-tailed) of 0.000 so that Ho was rejected, while the average N-Gain result was 0.66 in the category of moderate improvement. It can be concluded that Problem Posing-Based Android Applications are proven to be valid and suitable for use in learning.